Elicitors of Host Plant Defenses Partially Suppress Cacopsylla pyricola (Hemiptera: Psyllidae) Populations Under Field Conditions. Issue 2 (29th March 2017) - Cooper, W. Rodney; Horton, David R.
Abstract: Defense elicitors are products that activate acquired defense responses in plants, thus rendering the plants less susceptible to attack by a broad range of pests. We demonstrated previously under laboratory conditions that foliar applications of the defense elicitors Actigard (acibenzolar- S -methyl), Employ (harpin protein), or ODC (chitosan) to potted pear trees ( Pyrus communis L.) each caused an increase in mortality of Cacopsylla pyricola (Förster) (Hemiptera: Psyllidae) nymphs and altered the settling and oviposition behavior of the adults. In this study, we monitored C. pyricola populations over a 3-yr period on orchard-grown trees treated with water (untreated control), Actigard, Employ, or ODC. Fewer nymphs were observed on trees treated with elicitors compared with untreated trees in both 2014 and 2016. A similar but statistically nonsignificant pattern was observed in 2015 when nearly 30% fewer nymphs were observed on trees treated with elicitors versus untreated controls. Observed reductions in psyllid numbers by defense elicitors were modest and do not warrant the use of these products alone for managing C. pyricola . However, these products are often used for management of fire blight, and our observations that elicitors also reduce C. pyricola populations may be useful for system-wide integrated pest management approaches.